Rice Paddies Reduce Subsequent Yields of Wheat Due to Physical and Chemical Soil Constraints - Yang, Rui; Wang, Zhuangzhi; Fahad, Shah; Geng, Shiying; Zhang, Chengxiang; Harrison, Matthew Tom; Adnan, Muhammad; Saud, Shah; Zhou, Meixue; Liu, Ke; Wang, Xiaoyan (Frontiers in Plant Science, 2022)
Post-rice wheat yields are generally low in paddy soils that undergo radical changes in chemical and physical properties. However, it is not clear whether such low yields are related with constrained root growth caused by post-paddy soils. To investigate this, field experiments were conducted in Jianghan Plain under four nitrogen treatments with different application rates and timing to analyze the differences in soil properties and the spatial distribution of wheat roots between rice-wheat rotation and dryland cropping rotation of wheat season. Soil saturated water capacity and non-capillary porosity were significantly higher in dryland crop-wheat (DW) than rice-wheat (RW) cropping system. In contrast, the soil bulk density was significantly higher in RW than DW. Soil available nitrogen (AN) and organic matter were comparatively higher in in DW than RW irrespective of nitrogen application time while in contrast, soil available P and K were higher under RW than DW both at anthesis and post-harvest stages. The effect of cropping system was non-significant for soil pH. At anthesis stage, the root length percentage (RLP) was relatively more concentrated in surface (0-20 cm) in RW than DW cropping system in 0-20 cm while, at 20-40 cm and 40-60 cm it was higher in DW than RW for all N treatments. At harvesting, the root length percentage (RLP) were ranked as 0-20 > 20-40 > 40-60 cm under both cropping systems irrespective of N fertilization. Correlation analysis of root length percentage (RLP) and soil chemical properties at 0-20cm depth indicated a significantly high positive correlation (r = 0.79 at anthesis, r = 0.68 at post-harvest) between soil available P (AP) and RLP while, Available N (r= -0.59) and SOM (r= -0.39) were negatively correlated with RLP at anthesis. Nitrogen applied at the rate of 180 kg ha−1 in three split, 60 kg N ha−1 each at sowing, wintering and jointing performed better than the rest of N application rates and time under both cropping system and shall be adopted subject to further verification under diverse agro-climatic conditions.